Bioresorbable bone implant materials
By making homemade modified hydroxyapatite and functional copolymer, combined with formula design and molding process, a bioabsorbable bone implant material was prepared, which solved the problem of acidic products generated by the degradation of polylactic acid implant materials and improved bone integration. capacity and bone density, enabling more effective bone repair and material stability.
Patent Information
- Application Number
- CN202410974293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing polylactic acid implant materials produce acidic products upon degradation, resulting in sterile inflammatory reactions and material deterioration, and the material has low osseous binding ability and no bone conductivity.
A bioabsorbable bone implant material was prepared through molecular design of homemade modified hydroxyapatite and functional copolymers, combined with formula design, granulation and injection molding. Modified hydroxyapatite improves its osteoinductive ability and compatibility through strontium doping and amino acid surface modification; functional copolymer enhances its acid suppression, promotes bone growth and Repair function.
This material can effectively neutralize lactic acid produced by the degradation of polylactic acid, improve bone bonding capacity and bone density, reduce inflammatory reactions caused by acidic products, extend the service life of the material, and promote bone repair.
Smart Images

Figure BDA0004954098070000161 
Figure BDA0004954098070000171
Abstract
Description
Technical Field
[0001] The invention relates to a bioabsorbable bone implant material and belongs to the field of biocomposite materials. Background Art
[0002] Polylactic acid, also known as polylactide, is a synthetic biodegradable polymer material with the earliest research, the most mature technology and the most applications. As a recognized safe material approved by the U.S. Food and Drug Administration (FDA), polylactic acid has a high potential for biomedical applications. At present, medical devices made of polylactic acid and its composite materials are gradually being developed and applied, such as disposable syringes, bone fixation devices, surgical sutures and tissue repair materials. Especially in orthopedic clinical applications, compared with traditional metal bone fixation materials, polylactic acid biomaterials have shown two great advantages: they can be degraded and absorbed in the body after implantation, avoiding secondary surgery; the strength of polylactic acid decreases with degradation, overcoming stress shielding and improving the effect of bone injury fixation and repair.
[0003] Although it has been widely used in clinical practice, there are still certain problems in practical applications. The main reasons are that the material has low bone bonding ability and lacks bone conductivity. The acidic products generated by the degradation of the product after implantation in the human body can cause aseptic inflammatory reactions and even aseptic bone tissue necrosis. At the same time, the acidic products can promote self-accelerated degradation of the material.
[0004] Hydroxyapatite is the main mineral component in bone tissue. Chemically synthesized hydroxyapatite bioceramics are not only safe and non-toxic, but also have good biocompatibility and are beneficial to bone conduction. At the same time, after being implanted into the animal body, the bone and the material can be directly fused. The degradation product of hydroxyapatite is weakly alkaline and can neutralize the lactic acid produced by the degradation of polylactic acid, but it has poor toughness, is brittle, and has poor load-bearing capacity.
[0005] Therefore, considering the problem of free acid generated by existing polylactic acid used in implant materials and the characteristics of hydroxyapatite, a new composite material can be designed with polylactic acid and hydroxyapatite as the main body, which can solve the problem of free acid generated by polylactic acid degradation and the brittleness of inorganic materials. However, it also produces the compatibility problem of organic and inorganic materials, and solving the compatibility problem becomes the key. Summary of the invention
[0006] The purpose of the present invention is to provide a bioresorbable bone implant material and a preparation method thereof to solve the problem that the acidic products generated by the degradation of polylactic acid implant materials in the prior art will lead to aseptic inflammatory reactions and deteriorate the materials to cause failure. The present invention prepares modified hydroxyapatite and functional copolymers by molecular design, and then granulates and injects them into the materials through formula design. The technical solution adopted by the present invention to solve the technical problem is:
[0007] A method for preparing modified hydroxyapatite comprises the following steps:
[0008] S11, reacting monohydrogen phosphate, strontium salt and calcium salt to obtain intermediate product 1I;
[0009] S12, subjecting the intermediate product 1I to a surface modification reaction with an amino acid to obtain modified hydroxyapatite.
[0010] Furthermore, the monohydrogen phosphate, strontium salt and calcium salt are added in a mass ratio of monohydrogen phosphate, strontium ion and calcium ion of 3.0g:0.2-0.6g:1.7-1.9g.
[0011] Further, the ratio of the intermediate product II to the amino acid is 10 g: 4.0-5.0 g; and
[0012] The amino acids are basic amino acids.
[0013] The present invention also provides a modified hydroxyapatite prepared by the above-mentioned preparation method.
[0014] Another object of the present invention is to provide a method for preparing a functional copolymer, comprising the following steps:
[0015] S21, subjecting lactic acid, carboxylated catechol derivatives and epoxy acrylate to a ring-opening reaction to obtain an intermediate product 2I;
[0016] S22, mixing the zwitterion with magnesium bromide to obtain the intermediate 2II;
[0017] S23, subjecting the intermediate product 2I and the intermediate product 2II to free radical polymerization to obtain a functional copolymer.
[0018] Furthermore, the lactic acid, the carboxylated catechol derivative and the epoxy acrylate are added in a molar ratio of the total amount of carboxyl groups to the epoxy groups of 1:1; and,
[0019] The usage ratio of the lactic acid and the carboxylated catechol derivative is 0.5-0.8 mol: 0.2-0.5 mol.
[0020] Furthermore, the zwitterion is phosphorylcholine or betaine.
[0021] Furthermore, the usage ratio of the intermediate product 2I and the intermediate product 2II is 0.5-0.7 mol: 0.3-0.5 mol.
[0022] The present invention also provides a functional copolymer prepared by the above preparation method.
[0023] Another object of the present invention is to provide a bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0024] Polylactic acid 50-75 parts;
[0025] 20-40 parts of modified hydroxyapatite;
[0026] Functional copolymer 5-10 parts.
[0027] Furthermore, the weight average molecular weight of the polylactic acid is 200 kDa-500 kDa.
[0028] Another object of the present invention is to provide a method for preparing a bioabsorbable bone implant material, comprising the following steps:
[0029] S31, mixing, i.e.
[0030] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0031] S32, granulation, i.e.
[0032] placing the mixed raw materials in an extruder, melt blending, extruding, and pelletizing; and
[0033] S33, injection molding, i.e.
[0034] The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
[0035] Beneficial effects of the present invention:
[0036] (1) The present invention provides a bioresorbable bone implant material, the formula system contains homemade modified hydroxyapatite, which is hydroxyapatite doped with strontium and surface-modified with amino acids. First, hydroxyapatite is similar to the inorganic components of bone matrix and has good adhesion to bones; second, strontium is a trace element necessary for the human body, and strontium-doped hydroxyapatite has excellent bone induction ability, biocompatibility and biodegradability; third, after surface modification with amino acids, the modified hydroxyapatite has good compatibility in organic matrices; fourth, amino acids have excellent antibacterial properties; fifth, hydroxyapatite modified with basic amino acids has a certain alkalinity and has an excellent neutralizing effect on lactic acid produced by degradation of polylactic acid.
[0037] (2) The present invention provides a bioresorbable bone implant material, the formula system contains a self-made functional copolymer, which is a copolymer containing a catechol structure, lactic acid, and zwitterions containing bromide ions and magnesium ions. First, the lactic acid and catechol structures can have excellent volume expansion effects, improving the surface bonding between polylactic acid and modified hydroxyapatite; second, the catechol structure has excellent bonding properties in a wet environment, effectively adhering to tissue cells in the body, etc., to promote healing and recovery; third, the magnesium ions in the zwitterion structure have the effect of promoting bone remineralization, which is beneficial to promoting bone growth and repair; the bromide ions have the function of inducing chondrocyte regeneration and differentiation, and can effectively promote cartilage repair; fourth, the quaternary ammonium salt structure in the zwitterion has a broad-spectrum antibacterial effect.
[0038] (3) The present invention provides a bioresorbable bone implant material. After formula design, the homemade modified hydroxyapatite and functional copolymer contain a large amount of hydroxyl or amino structures, which can form hydrogen bonds with polylactic acid and have excellent dispersibility and plasticity. At the same time, the free acid generated by degradation can be captured, which has a further acid-suppressing effect.
[0039] (4) The present invention provides a method for preparing a bioabsorbable bone implant material. The modified hydroxyapatite and functional copolymer in the formula system are prepared using common raw materials, and the preparation process is simple, which is conducive to the industrialization of the product of the present invention and has strong operability. DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0041] The purpose of the present invention is to develop a bioresorbable bone implant material to solve the problem of acidic products generated by the degradation of existing polylactic acid implant materials. The idea of implementation is: using hydroxyapatite as the main acid-inhibiting substance, surface modification of hydroxyapatite to meet its dispersibility in the polymer system; at the same time, a functional copolymer is made to have the properties of auxiliary acid inhibition and compatibility. For modified hydroxyapatite, specifically: considering that strontium is a trace element required by the human body and has the effect of promoting osteogenesis, strontium is doped into hydroxyapatite, and then surface modification is performed with amino acids; for functional copolymers, specifically: first, lactic acid and catechol are used as copolymer monomers to meet the compatibility with polylactic acid and the adsorption with modified hydroxyapatite, and at the same time, the catechol structure can effectively adhere to cells and promote proliferation. In addition, the introduction of zwitterions can simultaneously provide quaternary ammonium salt structure (antibacterial), magnesium ions (promoting osteogenesis), bromide ions (promoting bone tissue formation) and other structures. The theoretical basis for the realization is: to modify hydroxyapatite, firstly, strontium is involved in the precipitation reaction of hydroxyapatite, and then the carboxyl group in the amino acid is subjected to a condensation modification reaction with the hydroxyl group on the surface of hydroxyapatite to prepare; the functional copolymer is first subjected to a ring-opening reaction of lactic acid, carboxyl-containing catechol structure and epoxy acrylate; then the zwitterion is subjected to an ion exchange reaction with magnesium bromide; and finally the reaction product is subjected to free radical polymerization to prepare. The above-mentioned modified hydroxyapatite and the functional copolymer act synergistically with each other and have excellent acid inhibition, compatibility, antibacterial properties, promotion of osteogenesis and other multifunctional properties. The embodiments of the present invention are as follows:
[0042] The embodiment of the present invention provides a method for preparing modified hydroxyapatite, comprising the following steps:
[0043] S11, add monohydrogen phosphate to deionized water A, add strontium salt to deionized water B, add calcium salt to deionized water C, adjust pH to 9.0-11.0 with alkali solution respectively; heat to 80-100℃, mix calcium salt solution and strontium salt solution, add dropwise to monohydrogen phosphate solution, control the dropwise rate to 0.5-1.0 drops / s, continue stirring for 3-5h after the dropwise addition is completed; ultrasonically disperse, let stand for 24h, settle, filter, and take insoluble matter. Wash with deionized water D 3 times, dry at 50℃ for 1 week, put the dried block into a mortar and crush it to obtain intermediate product 1I.
[0044] The monohydrogen phosphate, deionized water A, strontium salt, deionized water B, calcium salt, deionized water C, and deionized water D are added according to the mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.2-0.6 g:100 mL:1.7-1.9 g:100 mL:400 mL.
[0045] The monohydrogen phosphate may be diammonium hydrogen phosphate, disodium hydrogen phosphate, etc.; and preferably diammonium hydrogen phosphate;
[0046] The strontium salt may be strontium nitrate, etc., and preferably strontium nitrate;
[0047] The calcium salt may be calcium nitrate, calcium chloride, etc.; and preferably calcium nitrate;
[0048] The alkali solution may be aqueous ammonia, sodium hydroxide, etc., and aqueous ammonia is preferred.
[0049] S12, the intermediate product 1I is placed in deionized water E, ultrasonicated for 0.5h, stirred at 40-50°C for 3-5h, heated to 60-80°C, and a deionized water F solution containing amino acids is added, and the mixture is reacted for 1-2h; the mixture is cooled to room temperature, filtered, washed with deionized water G for 3 times, dried at normal pressure for 12h, and vacuum dried at 90°C for 12h to obtain modified hydroxyapatite.
[0050] The usage ratio of the intermediate product 1I, deionized water E, amino acid, deionized water F, and deionized water G is 10g:150mL:4.0-5.0g; 100mL:300mL.
[0051] The amino acid is a basic amino acid; it may be arginine, lysine, histidine, etc.; and lysine is preferred.
[0052] The present invention also provides a method for preparing a functional copolymer, comprising the following steps:
[0053] S21, protected from light, add lactic acid, carboxylated catechol derivative, epoxy acrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 18-24 hours; cool to room temperature, distill under reduced pressure, take the concentrate and vacuum dry it at 40°C for 12 hours to obtain the intermediate product 2I.
[0054] The lactic acid, carboxylated catechol derivative and epoxy acrylate are added in a molar ratio of the total amount of carboxyl groups to the epoxy groups of 1:1; and
[0055] The ratio of lactic acid to carboxylated catechol derivative is 0.5-0.8 mol: 0.2-0.5 mol;
[0056] The usage ratio of the epoxy acrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0057] The amount of the polymerization inhibitor used is 0.2 wt % of the epoxy acrylate; and the polymerization inhibitor in the following embodiments of the present invention is p-hydroxyanisole.
[0058] The carboxylated catechol derivatives may be protocatechuic acid, protocatechuic acid, gallic acid, dihydrocaffeic acid, danshensu, etc., and preferably gallic acid.
[0059] The epoxy acrylate may be glycidyl methacrylate or (glycidyloxy)ethyl methacrylate, etc., and preferably glycidyl methacrylate.
[0060] S22, protected from light, add the zwitterion to deionized water H, add magnesium bromide, ultrasonicate for 0.5h, stir at room temperature for 3-5h, let stand, distill under reduced pressure, add acetonitrile to produce a precipitate, filter, take the insoluble matter, and vacuum dry at 40°C for 12h to obtain the intermediate product 2II.
[0061] The dosage ratio of the zwitterion, deionized water H, magnesium bromide and acetonitrile is 0.1 mol:100 mL:0.05 mol:300 mL.
[0062] The zwitterion is phosphorylcholine or betaine;
[0063] The phosphorylcholine may be 2-methacryloyloxyethyl phosphorylcholine or the like;
[0064] The betaine may be methacryloylethyl sulfobetaine, acryloylethyl sulfobetaine or 4-[[2-(methacryloyloxy)ethyl]dimethylamino]butane-1-sulfonate, etc.
[0065] S23, add intermediate product 2I, intermediate product 2II and photoinitiator to N,N-dimethylformamide, irradiate under UV lamp for 10-50 minutes, remove UV lamp, distill under reduced pressure, add methanol to the concentrate to produce precipitate, filter, take the precipitate, and vacuum dry at 60°C for 8 hours to obtain a functional copolymer.
[0066] The usage ratio of the intermediate product 2I, the intermediate product 2II and N,N-dimethylformamide is 0.5-0.7 mol: 0.3-0.5 mol: 500 mL.
[0067] The amount of the photoinitiator is 1-5wt% of the total mass of the reactants;
[0068] The photoinitiator is a commonly used photoinitiator, which may be photoinitiator 1173, photoinitiator 184, photoinitiator 2959, photoinitiator 369 or photoinitiator TPO, etc.; and the photoinitiator described in the following embodiments of the present invention is photoinitiator 1173.
[0069] The UV light intensity is 200-600mW / cm 2 .
[0070] The zwitterions described in the present invention are based on phosphorylcholine or betaine, and are easy to form hydrophobic hydration with water, showing super-lubricating properties similar to ice surface, making it difficult for biological components such as proteins and liposomes to adhere to the surface of the material, and having excellent anti-cell adhesion; its mechanism is that the anions and cations in the zwitterions attract each other, exposing the hydrophobic structure in the molecule to form a hydrophobic hydration combination. In the present invention, zwitterions are used as raw materials, and ionized with magnesium bromide. Since the ionic radius of magnesium bromide is smaller than the anions and cations in the zwitterions, and the anions and cations in the zwitterions are combined with each other to form a ring structure with a certain ring tension, the bromide ions and magnesium ions formed by magnesium bromide in water are more likely to cross-combine with the anions and cations in the zwitterions to form a zwitterionic salt structure; finally, a hydrophilic effect is exhibited.
[0071] The self-made modified hydroxyapatite and functional copolymer of the present invention are applied to absorbable bone implant materials. Therefore, the embodiment of the present invention also provides a bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0072] Polylactic acid 50-75 parts;
[0073] 20-40 parts of modified hydroxyapatite;
[0074] Functional copolymer 5-10 parts.
[0075] The weight average molecular weight of the polylactic acid is 200kDa-500kDa; it can be 200kDa, 250kDa, 300kDa, 350kDa, 400kDa, 450kDa, 500kDa, or a range of any two values. The molecular weight of polylactic acid is greater than 500kDa, the mechanical properties will be improved but the processing difficulty is greater, and more plasticizers are required; the molecular weight is less than 200kDa, it is easy to process, but the mechanical properties are not good. The polylactic acid described in the following embodiments of the present invention was purchased from Shenzhen Guanghua Weiye Industrial Co., Ltd., and the average molecular weight
[0076] The polylactic acid is 50-75 parts, specifically 50 parts, 52 parts, 54 parts, 55 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 65 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 75 parts, or a range consisting of any two parts.
[0077] The modified hydroxyapatite is 20-40 parts, specifically 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts, 40 parts, or a range consisting of any two values.
[0078] The functional copolymer is 5-10 parts, specifically 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, or a range consisting of any two values.
[0079] In order to better understand the above invention, an embodiment of the present invention further provides a method for preparing a bioabsorbable bone implant material, comprising the following steps:
[0080] S31, mixing, i.e.
[0081] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0082] S32, granulation, i.e.
[0083] The mixed raw materials are placed in an extruder for melt blending, extrusion and pelletizing;
[0084] The extruder is a twin-screw extruder, the temperature of each zone is 160-210°C, and the temperature of the die head is 190-200°C.
[0085] S33, injection molding, i.e.
[0086] The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
[0087] The injection molding machine has an injection temperature of 170-220°C, a pressure of 1600-2000 bar, a holding time of 10-50 seconds, and a mold temperature of 30-45°C.
[0088] In order to further understand the present invention, a bioabsorbable bone implant material provided by the present invention is described in detail below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0089] Example 1
[0090] A method for preparing modified hydroxyapatite comprises the following steps:
[0091] S11, add diammonium hydrogen phosphate to deionized water A, add strontium nitrate to deionized water B, add calcium nitrate to deionized water C, and adjust the pH to 10.0 with ammonia water respectively; heat to 90°C, mix the calcium salt solution and the strontium salt solution, and add them dropwise to the monohydrogen phosphate solution, control the drop rate to 0.5-1.0 drops / s, and continue stirring for 4 hours after the dropwise addition is completed; ultrasonically disperse, let stand for 24 hours, settle, filter, and take the insoluble matter. Wash with deionized water D for 3 times, dry at 50°C for 1 week, put the dried block into a mortar and crush it to obtain the intermediate product 1I.
[0092] The diammonium hydrogen phosphate, deionized water A, strontium nitrate, deionized water B, calcium nitrate, deionized water C, and deionized water D are added in a mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.4 g:100 mL:1.8 g:100 mL:400 mL.
[0093] XRD test cell data are as follows: 532.53>527.47(HAp), since the ionic radius of strontium is larger than that of calcium, the unit cell volume expands, and strontium enters the hydroxyapatite lattice for doping.
[0094] Its infrared data is as follows: 3573cm -1 : -OH broad peak exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0095] S12, the intermediate product 1I is placed in deionized water E, ultrasonicated for 0.5 h, stirred at 45 °C for 4 h, heated to 70 °C, and a deionized water F solution containing lysine is added, and reacted for 1.5 h; cooled to room temperature, filtered, washed with deionized water G for 3 times, dried at normal pressure for 12 h, and vacuum dried at 90 °C for 12 h to obtain modified hydroxyapatite.
[0096] The usage ratio of the intermediate product 1I, deionized water E, lysine, deionized water F, and deionized water G is 10g:150mL:4.5g; 100mL:300mL.
[0097] Its infrared data is as follows: 3573cm -1 :-OH broad peak weakened; 3336cm -1 :-NH2 peak exists; 2921cm -1 :-CH2- exists; 2933cm -1 、2851cm -1 :-CH exists; 1735cm -1 :-C=O exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0098] A method for preparing a functional copolymer comprises the following steps:
[0099] S21, protected from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 18-24 hours; cool to room temperature, distill under reduced pressure, take the concentrate and place it under vacuum and dry it at 40°C for 12 hours to obtain the intermediate product 2I.
[0100] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0101] The dosage ratio of lactic acid to gallic acid is 0.6 mol:0.4 mol;
[0102] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0103] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0104] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1 : Epoxy group does not exist.
[0105] S22, protected from light, add 2-methacryloyloxyethyl phosphorylcholine to deionized water H, add magnesium bromide, ultrasonicate for 0.5h, stir at room temperature for 3-5h, let stand, distill under reduced pressure, add acetonitrile to produce precipitation, filter, take the insoluble matter, and vacuum dry at 40°C for 12h to obtain the intermediate product 2II.
[0106] The usage ratio of the 2-methacryloyloxyethyl phosphorylcholine, deionized water H, magnesium bromide and acetonitrile is 0.1 mol:100 mL:0.05 mol:300 mL.
[0107] Its infrared data are as follows: 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1608cm -1 、811cm -1 :-C=C- exists; 601cm -1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0108] S23, adding intermediate product 2I, intermediate product 2II, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 25 min, removing UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 h to obtain a functional copolymer ( PDI = 1.58).
[0109] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 0.6 mol: 0.4 mol: 500 mL.
[0110] The amount of the photoinitiator 1173 is 2 wt% of the total mass of the reactants;
[0111] The UV light intensity is 400mW / cm 2 .
[0112] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 601cm -1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0113] A bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0114] 62 parts of polylactic acid;
[0115] 30 parts of modified hydroxyapatite;
[0116] 8 parts of functional copolymer.
[0117] A method for preparing a bioabsorbable bone implant material comprises the following steps:
[0118] S31, mixing, i.e.
[0119] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0120] S32, granulation, i.e.
[0121] The mixed raw materials are placed in an extruder for melt blending, extrusion and pelletizing;
[0122] The extruder is a twin-screw extruder, and the temperatures of each zone are 160°C, 175°C, 185°C, 195°C, 205°C, and 205°C respectively; the die head temperature is 195°C.
[0123] S33, injection molding, i.e.
[0124] The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
[0125] The injection molding temperatures of the injection molding machine are 180°C, 195°C, and 210°C, respectively; the pressure is 1800 bar; the holding time is 30s; and the mold temperature is 40°C.
[0126] Example 2
[0127] The rest is the same as in Example 1, except that:
[0128] A method for preparing modified hydroxyapatite comprises the following steps:
[0129] S11, add diammonium hydrogen phosphate to deionized water A, add strontium nitrate to deionized water B, add calcium nitrate to deionized water C, and adjust the pH to 9.0 with ammonia water respectively; heat to 100°C, mix the calcium salt solution and the strontium salt solution, and add them dropwise to the monohydrogen phosphate solution, control the drop rate to 0.5-1.0 drops / s, and continue stirring for 3 hours after the dropwise addition is completed; ultrasonically disperse, let stand for 24 hours, settle, filter, and take the insoluble matter. Wash with deionized water D 3 times, dry at 50°C for 1 week, put the dried block into a mortar and crush it to obtain the intermediate product 1I.
[0130] The diammonium hydrogen phosphate, deionized water A, strontium nitrate, deionized water B, calcium nitrate, deionized water C, and deionized water D are added in a mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.6 g:100 mL:1.7 g:100 mL:400 mL.
[0131] XRD test cell data are as follows: 535.01>527.47(HAp). Since the ionic radius of strontium is larger than that of calcium, the unit cell volume expands and strontium enters the hydroxyapatite lattice for doping.
[0132] Its infrared data is as follows: 3573cm -1 : -OH broad peak exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0133] S12, the intermediate product 1I is placed in deionized water E, ultrasonicated for 0.5 h, stirred at 40°C for 5 h, heated to 60°C, and a deionized water F solution containing lysine is added, and reacted for 2 h; cooled to room temperature, filtered, washed with deionized water G for 3 times, dried at normal pressure for 12 h, and vacuum dried at 90°C for 12 h to obtain modified hydroxyapatite.
[0134] The usage ratio of the intermediate product 1I, deionized water E, lysine, deionized water F, and deionized water G is 10g:150mL:4.0g; 100mL:300mL.
[0135] Its infrared data is as follows: 3573cm -1 :-OH broad peak weakened; 3336cm -1 :-NH2 peak exists; 2921cm -1 :-CH2- exists; 2933cm -1 、2851cm -1 :-CH exists; 1735cm -1 :-C=O exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0136] A method for preparing a functional copolymer comprises the following steps:
[0137] S21, protected from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 18 hours; cool to room temperature, distill under reduced pressure, take the concentrate and vacuum dry it at 40°C for 12 hours to obtain the intermediate product 2I.
[0138] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0139] The dosage ratio of lactic acid to gallic acid is 0.6 mol:0.4 mol;
[0140] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0141] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0142] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm-1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1 : Epoxy group does not exist.
[0143] S22, protected from light, add 2-methacryloyloxyethyl phosphorylcholine to deionized water H, add magnesium bromide, ultrasonicate for 0.5h, stir at room temperature for 3-5h, let stand, distill under reduced pressure, add acetonitrile to produce precipitation, filter, take the insoluble matter, and vacuum dry at 40°C for 12h to obtain the intermediate product 2II.
[0144] The usage ratio of the 2-methacryloyloxyethyl phosphorylcholine, deionized water H, magnesium bromide and acetonitrile is 0.1 mol:100 mL:0.05 mol:300 mL.
[0145] Its infrared data are as follows: 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1608cm -1 、811cm -1 :-C=C- exists; 601cm -1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0146] S23, adding intermediate product 2I, intermediate product 2II, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 10 min, removing UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 h to obtain a functional copolymer ( PDI = 1.76).
[0147] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 0.6 mol: 0.4 mol: 500 mL.
[0148] The amount of the photoinitiator 1173 is 1wt% of the total mass of the reactants;
[0149] The UV light intensity is 600mW / cm 2 .
[0150] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1: benzene ring exists; 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 601cm -1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0151] Example 3
[0152] The rest is the same as in Example 1, except that:
[0153] A method for preparing modified hydroxyapatite comprises the following steps:
[0154] S11, add diammonium hydrogen phosphate to deionized water A, add strontium nitrate to deionized water B, add calcium nitrate to deionized water C, and adjust the pH to 11.0 with ammonia water respectively; heat to 80°C, mix the calcium salt solution and the strontium salt solution, and add them dropwise to the monohydrogen phosphate solution, control the drop rate to 0.5-1.0 drops / s, and continue stirring for 5 hours after the dropwise addition is completed; ultrasonically disperse, let stand for 24 hours, settle, filter, and take the insoluble matter. Wash with deionized water D for 3 times, dry at 50°C for 1 week, put the dried block into a mortar and crush it to obtain the intermediate product 1I.
[0155] The diammonium hydrogen phosphate, deionized water A, strontium nitrate, deionized water B, calcium nitrate, deionized water C, and deionized water D are added in a mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.2 g:100 mL:1.9 g:100 mL:400 mL.
[0156] XRD test cell data are as follows: 529.84>527.47(HAp), since the ionic radius of strontium is larger than that of calcium, the unit cell volume expands, and strontium enters the hydroxyapatite lattice for doping.
[0157] Its infrared data is as follows: 3573cm -1 : -OH broad peak exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0158] S12, the intermediate product 1I is placed in deionized water E, ultrasonicated for 0.5 h, stirred at 50°C for 3 h, heated to 80°C, and a deionized water F solution containing lysine is added, and reacted for 1 h; cooled to room temperature, filtered, washed with deionized water G for 3 times, dried at normal pressure for 12 h, and vacuum dried at 90°C for 12 h to obtain modified hydroxyapatite.
[0159] The usage ratio of the intermediate product 1I, deionized water E, lysine, deionized water F, and deionized water G is 10g:150mL:5.0g; 100mL:300mL.
[0160] Its infrared data is as follows: 3573cm -1 :-OH broad peak weakened; 3336cm -1 :-NH2 peak exists; 2921cm -1 :-CH2- exists; 2933cm -1 、2851cm -1 :-CH exists; 1735cm -1 :-C=O exists; 1033cm -1 、873cm -1 : Phosphate exists.
[0161] A method for preparing a functional copolymer comprises the following steps:
[0162] S21, protected from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat under reflux for 24 hours; cool to room temperature, distill under reduced pressure, take the concentrate and place it under vacuum at 40°C for 12 hours to obtain the intermediate product 2I.
[0163] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0164] The dosage ratio of lactic acid to gallic acid is 0.6 mol:0.4 mol;
[0165] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0166] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0167] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1: Epoxy group does not exist.
[0168] S22, protected from light, add 2-methacryloyloxyethyl phosphorylcholine to deionized water H, add magnesium bromide, ultrasonicate for 0.5h, stir at room temperature for 3-5h, let stand, distill under reduced pressure, add acetonitrile to produce precipitation, filter, take the insoluble matter, and vacuum dry at 40°C for 12h to obtain the intermediate product 2II.
[0169] The usage ratio of the 2-methacryloyloxyethyl phosphorylcholine, deionized water H, magnesium bromide and acetonitrile is 0.1 mol:100 mL:0.05 mol:300 mL.
[0170] Its infrared data are as follows: 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1608cm -1 、811cm -1 :-C=C- exists; 601cm -1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0171] S23, adding intermediate product 2I, intermediate product 2II, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 50 min, removing UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 h to obtain a functional copolymer ( PDI = 1.57).
[0172] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 0.6 mol: 0.4 mol: 500 mL.
[0173] The amount of the photoinitiator 1173 is 5wt% of the total mass of the reactants;
[0174] The UV light intensity is 200mW / cm 2 .
[0175] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1187cm -1 :-P=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 601cm-1 :Mg-O exists; 675cm -1 :-N-Br exists.
[0176] Example 4
[0177] The rest is the same as in Example 1, except that:
[0178] A method for preparing modified hydroxyapatite, in step S12,
[0179] The usage ratio of the intermediate product 1I, deionized water E, lysine, deionized water F, and deionized water G is 10g:150mL:4.0g; 100mL:300mL.
[0180] Example 5
[0181] The rest is the same as in Example 1, except that:
[0182] A method for preparing modified hydroxyapatite, in step S12,
[0183] The usage ratio of the intermediate product 1I, deionized water E, lysine, deionized water F, and deionized water G is 10g:150mL:5.0g; 100mL:300mL.
[0184] Example 6
[0185] The rest is the same as in Example 1, except that:
[0186] A method for preparing modified hydroxyapatite, in step S11,
[0187] The diammonium hydrogen phosphate, deionized water A, strontium nitrate, deionized water B, calcium nitrate, deionized water C, and deionized water D are added in a mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.6 g:100 mL:1.7 g:100 mL:400 mL.
[0188] Example 7
[0189] The rest is the same as in Example 1, except that:
[0190] A method for preparing modified hydroxyapatite, in step S11,
[0191] The diammonium hydrogen phosphate, deionized water A, strontium nitrate, deionized water B, calcium nitrate, deionized water C, and deionized water D are added in a mass volume ratio of monohydrogen phosphate, deionized water A, strontium ions, deionized water B, calcium ions, deionized water C, and deionized water D of 3.0 g:100 mL:0.2 g:100 mL:1.9 g:100 mL:400 mL.
[0192] Example 8
[0193] The rest is the same as in Example 1, except that:
[0194] A method for preparing a functional copolymer, in step S21,
[0195] The usage ratio of lactic acid to gallic acid is 0.5 mol:0.5 mol.
[0196] Example 9
[0197] The rest is the same as in Example 1, except that:
[0198] A method for preparing a functional copolymer, in step S21,
[0199] The usage ratio of the lactic acid to the gallic acid is 0.8 mol:0.2 mol.
[0200] Example 10
[0201] The rest is the same as in Example 1, except that:
[0202] A method for preparing a functional copolymer, in step S23,
[0203] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 0.5 mol: 0.5 mol: 500 mL.
[0204] Embodiment 11
[0205] The rest is the same as in Example 1, except that:
[0206] A method for preparing a functional copolymer, in step S23,
[0207] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 0.7 mol: 0.3 mol: 500 mL.
[0208] Example 12
[0209] The rest is the same as in Example 1, except that:
[0210] A method for preparing a functional copolymer, in step S23,
[0211] The 2-methacryloyloxyethyl phosphorylcholine was replaced with methacryloylethyl sulfobetaine.
[0212] Embodiment 13
[0213] The rest is the same as in Example 1, except that:
[0214] A bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0215] 50 parts of polylactic acid;
[0216] 40 parts of modified hydroxyapatite;
[0217] 10 parts of functional copolymer.
[0218] A method for preparing a bioabsorbable bone implant material comprises the following steps:
[0219] S31, mixing, i.e.
[0220] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0221] S32, granulation, i.e.
[0222] The mixed raw materials are placed in an extruder for melt blending, extrusion and pelletizing;
[0223] The extruder is a twin-screw extruder, and the temperatures of the zones are 160°C, 175°C, 185°C, 195°C, 200°C, and 195°C respectively; the die head temperature is 190°C.
[0224] S33, injection molding, i.e.
[0225] The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
[0226] The injection molding machine has injection temperatures of 170°C, 190°C, and 200°C, respectively, a pressure of 2000 bar, a holding time of 50s, and a mold temperature of 30°C.
[0227] Embodiment 14
[0228] The rest is the same as in Example 1, except that:
[0229] A bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0230] 75 parts of polylactic acid;
[0231] 20 parts of modified hydroxyapatite;
[0232] 5 parts of functional copolymer.
[0233] A method for preparing a bioabsorbable bone implant material comprises the following steps:
[0234] S31, mixing, i.e.
[0235] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0236] S32, granulation, i.e.
[0237] The mixed raw materials are placed in an extruder for melt blending, extrusion and pelletizing;
[0238] The extruder is a twin-screw extruder, and the temperatures of the zones are 160°C, 175°C, 195°C, 200°C, 210°C, and 210°C respectively; the die head temperature is 200°C.
[0239] S33, injection molding, i.e.
[0240] The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
[0241] The injection molding temperatures of the injection molding machine are 180°C, 200°C, and 220°C, respectively; the pressure is 1600 bar; the holding time is 10s; and the mold temperature is 45°C.
[0242] The following comparative examples of bioresorbable bone implant materials are compared with Example 1:
[0243] Comparative Example 1
[0244] The rest is the same as in Example 1, except that:
[0245] A bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0246] 62 parts of polylactic acid;
[0247] 8 parts of functional copolymer.
[0248] Comparative Example 2
[0249] The rest is the same as in Example 1, except that:
[0250] The modified hydroxyapatite was replaced with the intermediate product 1I in specific example 1, i.e., no basic amino acid was added for surface modification.
[0251] Comparative Example 3
[0252] The rest is the same as in Example 1, except that:
[0253] A method for preparing modified hydroxyapatite, in step S12, the lysine is replaced by glutamic acid (acidic amino acid).
[0254] Comparative Example 4
[0255] The rest is the same as in Example 1, except that:
[0256] A method for preparing modified hydroxyapatite, in step S11,
[0257] The strontium nitrate was replaced by calcium nitrate, ie, no strontium nitrate was added.
[0258] Comparative Example 5
[0259] The rest is the same as in Example 1, except that:
[0260] A bioabsorbable bone implant material, comprising the following raw materials in parts by weight:
[0261] 62 parts of polylactic acid;
[0262] 30 parts of modified hydroxyapatite.
[0263] Comparative Example 6
[0264] The rest is the same as in Example 1, except that:
[0265] A method for preparing a functional copolymer, in step S21,
[0266] The dosage ratio of the lactic acid to the gallic acid is 0 mol:1.0 mol, that is, no lactic acid is added.
[0267] Comparative Example 7
[0268] The rest is the same as in Example 1, except that:
[0269] A method for preparing a functional copolymer, in step S21,
[0270] The dosage ratio of lactic acid to gallic acid is 1.0 mol:0 mol, that is, no gallic acid is added.
[0271] Comparative Example 8
[0272] The rest is the same as in Example 1, except that:
[0273] A method for preparing a functional copolymer, in step S22,
[0274] The 2-methacryloyloxyethyl phosphorylcholine was replaced with methacryloyloxyethyl trimethylammonium chloride.
[0275] Comparative Example 9
[0276] The rest is the same as in Example 1, except that:
[0277] A method for preparing a functional copolymer, in step S23,
[0278] The usage ratio of the intermediate product 2I, the intermediate product 2II, and N,N-dimethylformamide is 1.0 mol: 0 mol: 500 mL, that is, the intermediate product 2I is not added.
[0279] Comparative Example 10
[0280] The rest is the same as in Example 1, except that:
[0281] In a method for preparing a functional copolymer,
[0282] The intermediate product 2II was replaced with 2-methacryloyloxyethyl phosphorylcholine, that is, magnesium bromide was not added to the reaction.
[0283] The physical properties of the bioabsorbable bone implant materials prepared in Examples 1-14 of the present invention and Comparative Examples 1-10 were measured respectively, and the results are shown in Table 1.
[0284] Table 1 Physical test performance of each embodiment
[0285]
[0286]
[0287] First, it can be concluded from Examples 1-14 in Table 1 that the bioresorbable bone implant material of the present invention has obvious advantages in reducing acidity, mechanical properties and antibacterial properties, and also has excellent properties such as promoting cell proliferation and differentiation and increasing bone density.
[0288] Second, it can be observed from Example 1 and comparative examples 1-4 that the bioabsorbable bone implant material of the present invention uses homemade modified hydroxyapatite, which has the advantages of effectively neutralizing acidity, improving mechanical properties, promoting bone tissue formation and increasing bone density; among them, it can be observed from comparative example 2 that the amino acid surface modification has excellent compatibility and plasticity, which can effectively improve the mechanical properties of the material; it can be observed from comparative example 3 that alkaline amino acids have obvious advantages in antibacterial properties; it can be observed from comparative example 4 that after strontium doping, hydroxyapatite can be promoted to remineralize and promote the improvement of bone density.
[0289] Third, it can be observed from Example 1 and comparative examples 5-10 that the bioabsorbable bone implant material of the present invention uses a self-made functional copolymer, which has the characteristics of promoting cell proliferation and differentiation, promoting bone tissue formation, and antibacterial properties; among them, it can be observed from comparative example 6 that the lactic acid structure has the advantages of enhancing compatibility and improving mechanical properties; from comparative example 7, it can be observed that the catechol structure has a certain promoting effect on cell adhesion and proliferation; from comparative examples 8-10, it can be observed that magnesium ions and phosphorus elements have a positive effect on bone tissue formation.
[0290] Fourth, it can be observed from Example 1 and Comparative Examples 1, 5, 8, and 9 that the modified hydroxyapatite and the functional copolymer have synergistic antibacterial properties, and it can be observed that the quaternary ammonium salt has a more excellent antibacterial effect. In addition, the modified hydroxyapatite and the functional copolymer also have synergistic acid inhibition because the metal ions and the amino groups synergistically have a capture function for free acids.
[0291] In summary, the bioresorbable bone implant material of the present invention uses homemade modified hydroxyapatite and functional copolymers, has obvious advantages in acid suppression, mechanical properties and antibacterial properties, and also has excellent properties such as promoting cell proliferation and differentiation and improving bone density.
[0292] The test method is as follows:
[0293] (1) Tensile strength: Tested according to the method described in GB / T 16421-1996.
[0294] (2) Flexural strength: Tested according to the method described in GB / T 16419-1996.
[0295] (3) OD value (cell proliferation): On the 10th day of ATDC5 cell culture, the CCK-8 kit (purchased from DOJINDO, Japan) was used to detect the proliferation of cells in different culture media. On the 10th day of cell culture, the original culture medium was aspirated, and 110 μL of culture medium mixed with CCK-8 reagent was added (10 mL of CCK-8 reagent was mixed in every 100 mL of DMEM / F12 culture medium), and incubated in an incubator for 45 min. After the reaction was completed, the absorbance at 450 nm was measured by an ELISA reader.
[0296] (4) Cell differentiation test: On the 7th day of ATDC5 cell culture, the content of glycosaminoglycan (GAG) secreted by the cultured ATDC5 cells differentiated into chondrocytes was quantitatively detected and the dsDNA (double-stranded DNA) content was measured. The content of dsDNA per microgram was calculated and the data was normalized.
[0297] Preparation of papain lysis buffer:
[0298] Dissolve the following ingredients in PBS: 50 mM Na3PO4, 20 mM Nacetyl cysteine, 28 μL / mL papain, filter through 0.22 μm filter membrane, and store at 4°C.
[0299] Lysis of cells:
[0300] Transfer the cultured monolayer cells or cultured cell clusters to the well plate, wash twice with PBS, add 300μL papain lysis solution to the well plate, seal the well plate with sealing film and keep it in a 60℃ water bath for 16h. After completion, centrifuge the well plate and mix the lysis solution by blowing with a 200μL pipette tip. Transfer the lysis solution to a 1.5mL EP tube, centrifuge and take the supernatant for immediate determination or store at -80℃ for later use. This sample is used for the determination of double-stranded DNA (ds DNA) and GAG content.
[0301] Determination of ds DNA content:
[0302] The lysate samples obtained by cell lysis were taken and the concentration of dsDNA was tested by Nanodrop instrument.
[0303] GAG content determination:
[0304] The lysate sample obtained by cell lysis was reacted with DMMB staining solution at a volume ratio of 1:6. After completion, the absorbance at 525 nm was detected on an ELISA reader and standardized with the ds DNA content to calculate the relative content of GAG per microgram of ds DNA.
[0305] (5) Antibacterial properties:
[0306] The in vitro antibacterial activity was tested using Escherichia coli (ATCC 25922) as follows:
[0307] The PBS buffer solution was used as the negative control group. The scaffolds in the experimental group were immersed in 500 μL of bacterial suspension (10 6 CFU / mL) in a 48-well cell culture plate, incubate at 37°C for 3 h, dilute the bacterial suspension with PBS buffer, and inoculate on lysogeny broth agar plates. The antibacterial activity was evaluated by counting the percentage of bacteria after 3 h using the CFU counting method.
[0308] (6) pH determination:
[0309] Prepare degradation medium: PBS solution, specifically PBS solution + 0.25% SDS; initial pH = 7.4 ± 0.2, place 0.1 g of the material to be tested in a sample bottle containing PBS, and place the sample bottle in a shaker at 37 ± 2 ° C. The ratio of the volume (mL) of the buffer solution to the mass (g) of the experimental sample is 2500:1. Measure the solution pH at 0d, 14d, and 28d, and record the pH changes during the degradation process.
[0310] (7) Bone mineral density (BMD):
[0311] Artificial periosteum for repair of critical defects in rat skull: This animal experiment was conducted in accordance with the guidelines of the Institutional Animal Care and Use Committee (IACUC). Seven-week-old adult male SD rats weighing 250 g to 300 g were selected for the experiment. The artificial periosteum material was prepared into a disc with a diameter of 5 mm and a thickness of 1 mm, and then irradiated and sterilized.
[0312] The steps for making critical defects in rat skulls are as follows: First, rats are anesthetized by intraperitoneal injection of 0.3 ml of physiological saline containing 10% chloral hydrate per 100 g of animal body weight. After the rats are anesthetized, the surgical site is prepared, fixed on the operating table, and the surgical site is disinfected with iodine. An incision of about 2.5 cm is made along the midline of the skull, and the scalp and subcutaneous tissue are pulled to one side with a blunt instrument. A 5 mm diameter circular drill bit (Bernal Dental, Britain) is used to make a defect on each side of the rat skull. During the process, physiological saline is continuously used for flushing and cooling, and care is taken not to injure the meninges under the skull. After the defect is made, each group of scaffold materials is placed and the wound is sutured layer by layer. After surgery, each rat is injected with 200,000 units of penicillin every day for 3 days.
[0313] Four weeks after surgery, the rats were killed by injection of an overdose of chloral hydrate anesthesia, the skull was removed, gently rinsed with saline, fixed with 4% paraformaldehyde for 24 hours, and then scanned with a micro-computed tomography (Micro-CT) scanner with an operating current of 313 μA, a voltage of 80 kV, and an image pixel of 17.4 μm. The collected data were used to reconstruct 3D tomographic images and analyze bone mineral density (BMD) based on Micro-CT images.
[0314] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A bioabsorbable bone implant material, characterized in that: The invention comprises the following raw materials in parts by weight: Polylactic acid 50-75 parts; 20-40 parts of modified hydroxyapatite; 5-10 parts of functional copolymer; Wherein, the preparation method of the functional copolymer comprises the following steps: S21, subjecting lactic acid, carboxylated catechol derivatives and epoxy acrylate to a ring-opening reaction to obtain an intermediate product 2I; S22, mixing the zwitterion with magnesium bromide to obtain the intermediate 2II; S23, subjecting the intermediate product 2I and the intermediate product 2II to free radical polymerization to obtain a functional copolymer; The ratio of the amount of lactic acid, carboxylated catechol derivative and epoxy acrylate is based on the molar ratio of the total amount of carboxyl groups to the epoxy groups. Add 1:1 ratio; and The ratio of lactic acid to carboxylated catechol derivative is 0.5-0.8 mol: 0.2-0.5 mol; The zwitterion is phosphorylcholine or betaine; The usage ratio of the intermediate product 2I and the intermediate product 2II is 0.5-0.7 mol: 0.3-0.5 mol.
2. The bioabsorbable bone implant material according to claim 1, characterized in that: The weight average molecular weight of the polylactic acid is 200 kDa-500 kDa.
3. The bioabsorbable bone implant material according to claim 1, characterized in that: The preparation method of the modified hydroxyapatite comprises the following steps: S11, reacting monohydrogen phosphate, strontium salt and calcium salt to obtain intermediate product 1I; S12, subjecting the intermediate product 1I to a surface modification reaction with an amino acid to obtain modified hydroxyapatite.
4. The bioabsorbable bone implant material according to claim 3, characterized in that: The usage ratio of the monohydrogen phosphate, strontium salt and calcium salt is 3.0g based on the mass ratio of monohydrogen phosphate, strontium ion and calcium ion: 0.2-0.6g: add 1.7-1.9g.
5. The bioabsorbable bone implant material according to claim 3, characterized in that: The ratio of the intermediate product II to the amino acid is 10 g: 4.0-5.0 g; and The amino acids are basic amino acids.
6. The method for preparing the bioabsorbable bone implant material according to any one of claims 1 to 5, characterized in that: The steps include: S31, mixing, i.e. Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials; S32, granulation, i.e. The mixed raw materials are placed in an extruder for melt blending, extrusion and pelletizing; as well as S33, injection molding, i.e. The particles obtained in S32 are placed in an injection molding machine and injection molded to obtain the bioabsorbable bone implant material.
Citation Information
Patent Citations
Injectable silk fibroin bone repair filling sustained-release material, and preparation method and application thereof
CN103041447A
Preparation method of polylactic acid-based degradable alveolar bone reticular stent material
CN117398516A